CONTENTS OF FAD (FLAVIN ADENINE DINUCLEOTIDE) AND TOTAL AMOUNT OFFLAVIN AT ALLOTRANSPLANTATION OF EMBRYONIC MUSCLE TISSUE AT RATS - S.N. Kobylnik; S.A. Petrov (European Scientific Journal, ESJ, 2014)
The article presents the results of the determination of FAD and common flavin at allotransplantation of embryonic muscle tissue and determination of it without replanting. In this case, fetal tissue allotransplantation does not affect the number of common flavins. In the abdominal muscle tissue the number of common flavins increased during surgery without replanting. Number of FAD as at allotransplantation as during surgery without replanting increased in the femoral muscle of adult rat, therefore allotransplantation had no effect on the researching parameter. In the abdominal muscle tissue of adult rat at surgery without slackening, the amount of FAD did not happen any changes, but during allotransplantation of embryonic muscle tissue the amount of FAD increased, therefore it can be assumed that allotransplantation leads to increasing of FAD synthesis from riboflavin in the abdominal muscle tissue of adult rat.